Numerical investigation of bending–torsion coupling effect on aeroacoustic noise of a flexible unmanned aerial vehicle propeller. (April 2023) - Choi, Yo-Seb; Hong, Suk-Yoon; Song, Jee-Hun
The recent explosion in interest into the use of UAVs for a wide range of commercial applications has also raised awareness of the issue of noise coming from UAVs. This paper introduces a method for predicting the aeroacoustic noise of a flexible UAV propeller while considering bending–torsion coupling. Numerical simulations of a flexible UAV propeller are conducted under hovering conditions to investigate the coupling effect on noise prediction using a fluid–structure interaction and acoustic model based on Formulation 1A of Farassat. The bending–torsion coupling leads to additional bending-induced torsional deformation along with considerable increases in noise and the overall sound pressure level. The results indicate that the noise evaluated without the coupling was underestimated compared to that evaluated with the coupling. Finally, the bending–torsion coupling is shown to be essential for precisely predicting the noise of a rotating flexible UAV propeller to respond to strengthening noise regulations.